POWER SAVINGS AT SCHOOLS - Bodrug N.S. (Problems of the Regional Energetics)
It is considered the question of carrying out power inspections at school of Amur Region. The causes of over-expenditures of power resources are established. There are shown actions, which have been carried as a result of the investigation, directed on decrease of the level of the expense of power resources.